PERLAKUAN AKUNTANSI REVALUASI AKTIVA TETAP SERTA DAMPAKNYA TERHADAP LAPORAN KEUANGAN (Studi Kasus pada PKP-RI Kabupaten Pamekasan) - Subhan, Subhan; Djasmiko, Moh Ratno (JURNAL AKUNTANSI DAN INVESTASI, 2017)
The historical implementation of cost will result in the value of fixed assets presented in the balance sheet does not reflect actual value due to a decline in real value due to a decline in the value of the rupiah against foreign currencies. In dealing with it, the company can apply policy on revaluation of fixed assets. This study aims to determine the accounting treatment of revaluation of fixed assets and its impact on the financial statements at PKP-RI Pamekasan district. This study use quantitative data in the form of financial statements consisting of balance sheet in 2014-2015 obtained from PKP-RI Pamekasan district. The analytical model used by categorizing and combining data on accounting treatment of revaluation of fixed assets (and analyzing the impact to financial statements). The result of the research shows that asset revaluation influence to financial report of PKP-RI of Pamekasan Regency that is on balance sheet, on the remaining asset, business asset increases because asset value keeps increasing while accumulated depreciation value decreases due to the abolished accumulation of declining fixed asset. On the liabilities side there is an increase due to the emergence of new accounts on the revaluation increment of fixed assets in equity.